Below are the steps to convert a number to base 6 from base 10

Ill illustrate by example and explain each step as I go.

First you will set up your problem. lets say we want to convert 200 to base 6

The problem will be set up as follows 200 = ____ x 6 + ____ in the first blank, ___ , we divide 200 by 6 and drop the remainder which is 33 which makes our problem look like this 200 = 33 x 6 +

now for the second blank we place the remainder, which we dropped in the first step which gives us this:

200 = 33 x 6 + 2

The next step is you take the 33 and repeat what you did in the first step and placing it under the first part of or problem like this

200 = 33 x 6 + 2

33 = 5 x 6 + 3

Then you take the 5 and do the same thing. and you end up with

200 = 33 x 6 + 2

33 = 5 x 6 + 3

5 = 0 x 6 + 5

You then will take the remainders and from bottom to top and you get 532

This method works when converting to other bases as well.